MRI observation of CO2-C3H8 hydrate-induced water migration in glass sand. (2nd November 2019) - Zheng, Jia-nan; Jiang, Lanlan; Wang, Pengfei; Zhou, Hang; Yang, Mingjun
Graphical abstract: Highlights: The first observation of water drawing and migration induced by CO2 -C3 H8 hydrate formation in glass sand by MRI. The location of CO2 -C3 H8 hydrate-induced water migration are uncertain, but growth features are similar. Water can be drawn from the surrounding sands by the local formation of CO2 -C3 H8 hydrates. Continuous hydrate growth towards the gas phase induces further upward-climbing of water. Abstract: Hydrate-induced water migration is an unusual behaviour that occurs in certain hydrate formation processes, such as in the formation of propane-containing hydrate. This study is the first to investigate the continuous, staged processes of constant-volume formation, constant-pressure reformation and exhaust dissociation of CO2 -C3 H8 hydrates using the magnetic resonance imaging (MRI) technique. Real-time MRI images indicate that the formation of CO2 -C3 H8 hydrates draw water from its surroundings, causing the local water saturation to increase. As the concentrated water can further form hydrates and extend to the gas phase, the water appears as though it climbs upward through the glass sand and hydrate zone towards the gas phase. Experiments under different formation pressures indicate that the locations of hydrate-induced water migration are uncertain and depend on hydrate nucleation. The evolution processes of hydrate-induced water migration under different initial pressures have good similarity. In addition, water migration will still occur during the reformation stage. The initial pressure has great effects on both the formation and dissociation of hydrate. In addition, faster dissociation may make the water move upward due to strong gas release. The findings in this study are significant to future research on propane-containing hydrate, especially for hydrate-based seawater desalination applications.